Narayana Guru - Datt, Gayatri M.; Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2022)
It was a time when the evils of the caste system cast a malevolent shadow over Kerala. The 'avarnas', as the low castes were called, lived on the fringes of a society that found their very shadow, polluting. It was at such a time that Narayana was born. As a child he shocked his elders by questioning the system. As a guru he strove to educate people in the oneness of God and the human race.
Keywords: Visionaries; Biography- Narayana Guru (1856-1928); Philosopher